«No bride is visible»? Immagini da Praeneste - Menichetti, Mauro (O T I V M, 2019)
A recent work by L.Bouke Van der Meer aims to explore the iconographical patterns visible on Praenestine mirrors and cistae. Contrary to my opinion, such images seem far from a nuptial perspective and from a meaningfully congruent horizon related to gestures and tools of the women. A particularly important set of images representing ‘Bathing at a Labrum’ is taken into consideration in order to show the absence of this perspective. In my opinion images are always a symbolic way aimed to display cultural values related to specific historical contexts. The pattern we define as ‘Bathing at a Labrum’ is particularly appropriate in order to put in evidence, for example, the meaning of charis, the code of the gaze, the Dionysiac happiness as symbol and omen of the nuptial perspective. We have to do with a coherent language of images including gestures and tools of the mundus muliebris.